Higher Education Administration: Case Study of a University in India - Jain, Trilok Kumar (Journal of Advanced Research in English & Education; Vol 8 No 4 (2023): Journal of Advanced Research in English and Education, 2023)
This article delves into the pivotal role of higher education administration, with a specific focus on a case study of Suresh Gyan Vihar University in India. In the context of developing countries, the scarcity of robust institutions in higher and technical education poses a significant challenge to fostering growth. The paper emphasizes the importance of studying academic administration to address this deficiency and contribute to the advancement of developing nations. The case study of Suresh Gyan Vihar University, established in 2008, provides insights into the institution’s rapid growth and reputation for quality leadership. The university’s success is attributed to strategic approaches, including a clear articulation and communication of its vision and mission. The iterative development of these foundational elements involves active participation from diverse stakeholders, fostering a shared sense of purpose and adaptability to evolving needs. The vision, mission, and values of the university underscore its commitment to sustainability, ethics, and industry-relevant education. The article discusses how the university engages in continuous refinement of these statements through various events, ensuring alignment with its evolving philosophy. Notably, the university places a strong emphasis on research, reflected in the establishment of dedicated research institutions and centers of excellence. The article also explores the university’s commitment to community engagement, where student communities play a crucial role in social development activities. The introduction of evaluation-based scores for discipline, professional competence, extracurricular activities, and community contributions underscores the institution’s holistic approach to student development. The day-to-day functioning of the university is guided by the Suresh Gyan Vihar University Act of 2008, providing a statutory framework for interaction among stakeholders. Decision-making processes involve key statutory bodies, such as the Academic Council, Executive Council, and Board of Management.